Investigating the phytochemical profile, biological potentials, morphological, and anatomical characteristics of Cyclotrichium origanifolium (Labill.) Manden. & Scheng. (Lamiaceae) from Turkey - Aydın, Bilge; Alkuyruk, Satuk Buğra; Tekman, Enes; Yuca, Hafize; Karadayı, Mehmet; Gülşahin, Yusuf; Çeçen, Ömer; Bona, Gülnur Ekşi; Demirci, Betül; Bona, Mehmet; Karakaya, Songül (Protoplasma, 2025)
Cyclotrichium origanifolium , a plant widely used in Eastern and Southern Anatolia for culinary purposes, was subject of this study, which aimed to comprehensively evaluate its potential therapeutic applications. This research stands out due to its holistic approach, combining morpho-anatomical studies, chemical, and biological analyses to explore antioxidant, antidiabetic, anticholinesterase, genotoxic, and anti-genotoxic effects of methanolic and aqueous extracts, as well as flowering aerial part essential oil. It is a perennial plant, typically ranging from 10 to 40 cm in height, with a suffrutescent and highly branched growth habit. Essential oils are produced within glandular trichomes. Oil, analyzed via GC–MS/MS, revealed 24 compounds accounting for 96.4% of oil, with isomenthone (52.4%), pulegone (23.4%), and β -pinene (9.5%) as predominant components. These findings are significant as they provide new insights into chemical composition of oils, particularly highlighting pharmacologically active compounds. Methanol extract exhibited superior antioxidant activity, correlated with high phenol and tannin content. Essential oil showed moderate inhibition of α -amylase (49.54%) and mild inhibition of acetylcholinesterase (11.84%) and butyrylcholinesterase (16.93%), suggesting potential in managing oxidative stress and neurodegenerative diseases. Study also conducted biosafety evaluations using Ames/ Salmonella and Allium tests, essential for assessing genotoxic and antigenotoxic potential of natural products. Notably, significant antimicrobial effects were identified, particularly against Pseudomonas aeruginosa and Enterococcus faecalis . Comprehensive analysis and discovery of significant bioactivities position this research as a valuable contribution to field, distinguishing it from previous studies on similar species. This study provides a foundational understanding of morpho-anatomical, pharmacological, biological properties of plant, opening avenues for future research.